Eye Diseases and Refractive Errors in Hargeisa, Somaliland and Implications for Human Resource Development for Eye Care - Ahmed Nur Ismail Ege, Hafeez-ur-Rahman, Muhammad Aslam Bhatti, Ayesha Sumera, Intzar Hussain, Mohamud Ahmed Mohamed (Pakistan Journal of Ophthalmology, 2018)
Purpose: To estimate the burden of eye diseases & refractive errors in Hargeisa, Somaliland and analyze the need for human resource development for eye care in this region. Study Design: Cross-sectional descriptive study. Place and Duration of Study: The study was conducted at Manhal Specialty Hospital, Hargeisa, Somaliland from 2014-2015. Material and Methods: All those patients who presented to the Ophthalmology out-patient department (OPD) were included in the study. Complete ocular assessment including clinical examination, refraction, visual field assessment and B scan ultrasonography was done to identify causes of the presenting eye problems. After completing the protocol the diagnosis was recorded. For the human resource development needs’ assessment the data were obtained from the Somaliland’s National Health Professions Commission database and the University of Hargeisa (UoH). Results: A total of 5327 patients participated in the study, 75% of whom were adults (n = 4003) and 54.53% (n = 2905) were women. Cataract was the commonest eye disease accounting for 28.93% (n = 1541) of the cases followed by conjunctival diseases (n = 1212, 22.75%) and refractive errors n = 1089, 20.44%). The most frequent refractive error was Myopia (n = 680 [12.77%]). Needs assessment for eye care human resource showed that there was only one trained Ophthalmologist in Hargeisa at the time of the study. This study is the first to report burden of various eye diseases in Hargeisa, Somaliland. Conclusion: The human resource needed to deal with this burden of ocular diseases is very scarce and needs to be strengthened to prevent visual impairment and to promote eye health in the region. Key Words: Refractive Errors, Blindness, Visual Impairment, Cataract, Human Resource